2006
DOI: 10.1111/j.1600-0560.2006.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of Epstein–Barr virus association with Merkel cell carcinoma

Abstract: Our findings suggest that EBV is not associated with MCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…MCC is a rare neuroendocrine tumour that appears primarily on UV‐exposed sites. The increased incidence of this cancer in immunosuppressed patients led researchers to posit the presence of associated viral infection, potentially HPV or EBV 149,150 . In early 2008 Feng et al.…”
Section: Merkel Cell Polyomavirus and Merkel Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…MCC is a rare neuroendocrine tumour that appears primarily on UV‐exposed sites. The increased incidence of this cancer in immunosuppressed patients led researchers to posit the presence of associated viral infection, potentially HPV or EBV 149,150 . In early 2008 Feng et al.…”
Section: Merkel Cell Polyomavirus and Merkel Cell Carcinomamentioning
confidence: 99%
“…The increased incidence of this cancer in immunosuppressed patients led researchers to posit the presence of associated viral infection, potentially HPV or EBV. 149,150 In early 2008 Feng et al identified a novel polyomavirus in eight of 10 MCC samples by digital transcriptome subtraction. This virus, MCV (also known as MCPyV), was integrated at various locations in the tumour genome in six of eight MCCs, 44 suggesting that infection and integration occurred in the cells before tumour cell expansion.…”
Section: Merkel Cell Polyomavirus and Merkel Cell Carcinomamentioning
confidence: 99%
“…Size of primary tumor, stage of disease at presentation and pathologic nodal status are predictors of survival (Allen et al 2005). Shaw et al 2006), it is as yet unknown if other oncogenic viruses play a role. There is no characteristic cytogenetic abnormality in MCC (Manor et al 2006).…”
Section: Diagnosis and Stagingmentioning
confidence: 97%
“…Neben einer hohen kumulativen UV-Licht-Belastung der Haut (60-70% aller MZK finden sich im KopfHals-Bereich, 20-30% an den Extremitäten) [8] gilt die Immunsuppression als wichtigster Risikofaktor. HIV-Infizierte beispielsweise haben ein 13fach erhöh-tes Risiko [45]. Eine chronische Arsenintoxikation wird ebenfalls als Kofaktor für die Entwicklung von MZK angesehen [31].…”
Section: äTiologie Und Pathogeneseunclassified